Impact of Accounting Information System Implementation, Digital Transformation, and Internal Control on Employee Performance: A Case Study of PT Fokus Jasa Mitra - Widiantoro, Nawaal Fakhri; Akbar, Fajar Syaiful (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose : This study investigates the effects of Accounting Information System (AIS) implementation, digital transformation, and internal control on employee performance at PT Fokus Jasa Mitra. Methodology: A quantitative method was employed, utilizing a questionnaire distributed to 97 respondents. The data were analyzed using multiple linear regression to test the hypothesis. Results: The implementation of AIS, digital transformation, and internal control significantly affected employee performance, both partially and simultaneously. Findings: The study confirms that AIS, digital transformation, and internal controls contribute to employee performance through improved work efficiency and decision-making. Novelty: This study provides a unique perspective on how the interplay between technological and control factors impacts employee performance within the context of PT Fokus Jasa Mitra, a company transitioning from FoxPro to ERP. Originality: Unlike previous studies, this research specifically focuses on PT Fokus Jasa Mitra and uses SEM-PLS analysis to explore employee performance in light of system and organizational changes. Conclusion: The findings highlight the critical role of AIS, digital transformation, and internal control in enhancing employee performance. These insights offer practical implications for managers in similar business environments. Type of Paper: Empirical Research